Transcranial magnetic stimulation probes the excitability of the primary motor cortex: A framework to account for the facilitating effects of acute whole-body exercise on motor processes - Karen Davranche; John Temesi; Samuel Verges; Thierry Hasbroucq (Elsevier, 2015)
The effects of exercise on decision-making performance have been studied using a wide variety of cognitive tasks and exercise interventions. Although the current literature supports a beneficial influence of acute exercise on cognitive performance, the mechanisms underlying this phenomenon have not yet been elucidated. We review studies that used single-pulse transcranial magnetic stimulation (TMS) to probe the excitability of motor structures during whole-body exercise and present a framework to account for the facilitating effects of acute exercise on motor processes. Recent results suggest that, even in the absence of fatigue, the increase in corticospinal excitability classically reported during submaximal and exhausting exercises may be accompanied by a reduction in intracortical inhibition. We propose that reduced intracortical inhibition elicits an adaptive central mechanism that counteracts the progressive reduction in muscle responsiveness caused by peripheral fatigue. Such a reduction would render the motor cortex more sensitive to upstream influences, thus causing increased corticospinal excitability. Furthermore, reduction of intracortical inhibition may account for the more efficient descending drive and for the improvement of reaction time performance during exercise. The adaptive modulation in intracortical inhibition could be implemented through a general increase in reticular activation that would further account for enhanced sensory sensitivity.